Diffusion and adoption of technological innovations in Mar del Plata cooperative sector: the invisibility of their work - Zanfrillo, Alicia Inés (2018)
The contagion of innovations originates in small groups of pioneers that influence a larger group known as imitators, developing a channel of great influence on the next ones interested in the incorporation of a product or service. In the emerging Argentine market the adoption of technologies is explained by the imitation effect rather than by a few precursors. The advantage of knowing the potential market for a new technology allows the definition of policies that facilitate its propagation in the target groups. The purpose of the work is to model the behavior of Mar del Plata cooperative sector in the access to internet resources in order to promote the dissemination of these technologies on the market potential. From the marketing perspective, a quantitative research of a descriptive type with techniques of secondary source analysis is undertaken to obtain, with the mathematical formulation of Bass (1968), the parameters of the speed of adoption of the presence of internet. Subsequently, an agent-based approach was used to simulate the incorporation into the Information Society considering: a) the dynamic nature of the potential market given the permeability to the life cycle of these entities and b) the presence of complementary products such as social media. The resulting adoption curve resembles the original one in a slow penetration of the market, constituting a challenge to promote its inclusion in the new economy.